Association between atherogenic index of plasma and cognitive impairment in middle-aged and older adults: results from CHARLS - Zhou, Juan; Han, Han; Bai, Weimin (Frontiers in Aging Neuroscience, 2025)
BackgroundThe atherogenic index of plasma (AIP) has been proposed as a novel biomarker predictor for dyslipidemia and has been linked to various diseases. In this study, we explored the relationship between AIP levels and cognitive impairment in a middle-aged and older population.MethodsThis study utilized data from the China Health and Retirement Longitudinal Study (CHARLS) for 7,918 individuals aged 45 and older. The AIP was calculated as the logarithmic ratio of triglycerides to high-density lipoprotein cholesterol. To assess the relationship between the AIP and cognitive impairment, logistic regression models were employed, while restricted cubic spline analysis was conducted to explore potential non-linear associations between AIP levels and cognitive impairment.ResultsThe study participants had a mean age of 58.4 ± 8.8 years, and 49.1% were female. From 2011 to 2018, 2,911 participants (36.8%) developed cognitive impairment. After adjusting for potential confounders, the AIP was found to be significantly associated with cognitive impairment. In particular, participants in the higher AIP quartiles (Q2: odds ratio [OR]: 1.45, 95% confidence interval [CI]: 1.24–1.69, P < 0.001, Q3: OR: 1.63, 95% CI: 1.40–1.91, P < 0.001, and Q4: OR: 1.68, 95% CI: 1.43–1.98, P < 0.001) showed an increased risk of cognitive impairment compared to those in the lowest quartile (Q1). Additionally, a non-linear relationship was observed between AIP levels and cognitive impairment risk (P for nonlinear < 0.001).ConclusionThe study finds that elevated AIP levels are linked to an increased risk of cognitive impairment in middle-aged and older adults, suggesting that managing dyslipidemia could help reduce this risk.